Music-evoked incidental happiness modulates probability weighting during risky lottery choices - Schulreich, Stefan; Heussen, Yana G.; Gerhardt, Holger; Mohr, Peter N.; Binkofski, Ferdinand C.; Koelsch, Stefan; Heekeren, Hauke R. (Frontiers in Psychology, 2014)
We often make decisions with uncertain consequences. The outcomes of the choices we make are usually not perfectly predictable but probabilistic and the probabilities can be known or unknown. Probability judgments, i.e., the assessment of unknown probabilities can be influenced by evoked emotional states. This suggests that also the weighting of known probabilities in decision making under risk might be influenced by incidental emotions, i.e., emotions unrelated to the judgments and decisions at issue. Probability weighting describes the transformation of probabilities into subjective decision weights for outcomes and is one of the central components of cumulative prospect theory (CPT) that determine risk attitudes. We hypothesized that music-evoked emotions would modulate risk attitudes in the gain domain and in particular probability weighting. Our experiment featured a within-subject design consisting of four conditions in separate sessions. In each condition, the 41 participants listened to to a different kind of music—happy, sad, or no music, or sequences of random tones—and performed a repeated pairwise lottery choice task. We found that participants chose the riskier lotteries significantly more often in the “happy” than in the “sad” and “random tones” conditions. Via structural regressions based on CPT, we found that the observed changes in participants’ choices can be attributed to changes in the elevation parameter of the probability weighting function: In the “happy” condition, participants showed significantly higher decision weights associated with the larger payoffs than in the “sad” and “random tones” conditions. Moreover, the elevation parameter correlated positively with self-reported music-evoked happiness. Thus, our experimental results provide evidence in favor of a causal effect of incidental happiness on risk attitudes that can be explained by changes in probability weighting.